2016
DOI: 10.1515/crelle-2016-0012
|View full text |Cite
|
Sign up to set email alerts
|

Universal K-matrix for quantum symmetric pairs

Abstract: Let g be a symmetrizable Kac-Moody algebra and let Uq(g) denote the corresponding quantized enveloping algebra. In the present paper we show that quantum symmetric pair coideal subalgebras Bc,s of Uq(g) have a universal K-matrix if g is of finite type. By a universal K-matrix for Bc,s we mean an element in a completion of Uq(g) which commutes with Bc,s and provides solutions of the reflection equation in all integrable Uq(g)-modules in category O. The construction of the universal K-matrix for Bc,s bears signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
213
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(214 citation statements)
references
References 35 publications
1
213
0
Order By: Relevance
“…On the other hand, there is a notion of quantum symmetric pair, (U, U ı ), where U ı is a coideal subalgebra of U. The algebra U ı allows for some freedom of choices of parameters; see Letzter [Le99] (also see [BK15]). We make a particular choice of the parameters for U ı in this paper depending on p and q.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, there is a notion of quantum symmetric pair, (U, U ı ), where U ı is a coideal subalgebra of U. The algebra U ı allows for some freedom of choices of parameters; see Letzter [Le99] (also see [BK15]). We make a particular choice of the parameters for U ı in this paper depending on p and q.…”
Section: Introductionmentioning
confidence: 99%
“…As we learnt from Weiqiang Wang, algebraic K-matrix for quantum symmetric pairs of type AIII/IV first appeared in [BW13]. The relationship between the Kmatrix in this section and the algebraic ones in [BaK16] is not clear. 5.6.…”
Section: Quiver Varieties and Symmetric Pairsmentioning
confidence: 92%
“…A new canonical basis was constructed for certain tensor modules of U ′ q (k) in [BW13], for idempotented U ′ q (k) in [BKLW,LW15], and finally a general theory of canonical basis for k of any type was obtained in [BW16]. These works have inspired many developments in various directions, such as categorification [BSWW] and K-matrix [BaK16]. In the work [BKLW], there is a geometric realization of U ′ q (k) of type AIII/AIV without black vertices by using n-step isotropic flag varieties, in the spirit of Beilinson, Lusztig and MacPherson's influential work [BLM].…”
Section: Introductionmentioning
confidence: 99%
“…Recall that various versions of the reflection equation appeared in the works [Nou96,NS95,NDS97,Dij96]. It was only later realised by M. Balagovic and S. Kolb, through their algebraic construction of universal K-matrices, that there is a general framework of twisted reflection equations which unifies all different reflection equations [BK,Remark 9.7]. For a quasi-triangular Hopf algebra H with coideal subalgebra B one fixes an additional Hopf algebra involution φ of H, such that (φ ⊗ φ)(R) = R, called the twist.…”
Section: The Reflection Equations Revisitedmentioning
confidence: 99%
“…From such a character they construct a quantum symmetric pair, streamlining the approach of Noumi-Sugitani-Dijkhuizen [KS09]. Furthermore, M. Balagovic and S. Kolb showed that any pair in Letzter's classification carries a canonical solution to a reflection equation, called a universal K-matrix [BK,Kol17]. Such solutions can be used for applications to low-dimensional topology in the spirit of the celebrated Reshetikhin-Turaev knot invariants [tD98,tDHO98].…”
Section: Introductionmentioning
confidence: 99%